FACTORS OF PERFOMANCE MANAGEMENT SYSTEM AND WORK MOTIVATION ON EMPLOYEE ENGAGEMENT THROUGH EMPLOYEE PERFORMANCE AS A MEDIATION VARIABLE - Nadya Rana (Business Finence Analyst Co.,, 2023)
This study aimed to identify Performance Management System (PMS), work motivation, and employee performance factors through employee engagement as mediation. Measuring the value of each performance achievement using the PLS SEM method. The research was conducted from March to April 2023. The data collected in this study were primary data obtained from an Indonesian-language questionnaire survey which was distributed via the Google form link using a Likert scale. The sampling method (respondents) used was quota sampling. Data is processed and analyzed using SEM-PLS. The results of the study obtained 240 respondents and showed that all variables had an effect. The managerial implication of this research is that state-owned banking companies in Indonesia are advised to increase their current employee engagement and pay attention to factors that can inhibit or reduce employee engagement to maintain company performance in the future. One of the factors that has an impact on the performance of employees and the company at this time is the occurrence of the Covid-19 pandemic and changes in the company's internal environment. Thus, communication between companies and employees must be maintained to minimize misunderstandings regarding their work. The ability of employees to manage emotions, control themselves and establish good relations with fellow co-workers will have an impact on improving performance both at work and in social life.